Building Character Through Scout Activities: A Study of Discipline, Responsibility, and Cooperation Development in Elementary Students - Indriyani, Ismi Safitri; Nurul Iman, Bagus; Faiz, Aiman (Papanda Publisher, 2025)
Character development in elementary education requires comprehensive approaches that extend beyond classroom instruction to include structured extracurricular activities. This study examines the effectiveness of scout extracurricular activities in developing student character, specifically investigating improvements in discipline, responsibility, and cooperation among elementary school students. A qualitative descriptive study was conducted at SDN 1 Astana from May to July 2025. Twenty students from grades IV and V who actively participated in scout activities were purposively selected as primary participants, along with three scout coaches, five classroom teachers, and the school principal as key informants. Data collection involved structured observations during scout meetings and school activities, semi-structured interviews with all participant categories, and document analysis of attendance records and student reflections. Thematic analysis was employed to identify patterns related to character development across the three target dimensions. The study documented significant improvements across all character dimensions following three months of regular scout participation. Discipline indicators showed substantial gains: punctuality increased by 25% (from 60% to 85%), uniform compliance improved by 33% (from 45% to 78%), and rule adherence increased by 27% (from 55% to 82%). Responsibility development was evidenced by task completion rates progressing from 50% to 83%, while cooperation skills demonstrated the most dramatic improvement with group participation rates increasing from 52% to 87%. Additionally, school disciplinary incidents decreased by 40% among scout participants, and character-related classroom behaviors improved by 30%. The findings support positive youth development frameworks, demonstrating that structured activities with sustained adult-youth relationships, clear expectations, and authentic leadership opportunities create effective contexts for comprehensive character development.